1984
DOI: 10.37570/bgsd-1984-33-14
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for the recognition of boundaries between Cretaceous stages by means of planktonic foraminiferal biostratigraphy

Abstract: Planktonic foraminifera are a much used biostratigraphic tool for the subdivision of the Cretaceous System from the Albian upwards. A proposal is given for the recognition of Cretaceous stages, using major biostratigraphic events to mark their boundaries. Thus, the extinction of Globotruncanita calcarata marks the Maastrichtian - Campanian boundary; the extinction of Dicarinel/a asymetrica the Campanian -Santonian boundary; the entry of D. asymetrica the Santonian - Coniacian boundary; the entry of Dicarinella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 5 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Caron M. [16] established this zone to represent the early Coniacian and occupy the interval from the first occurrence of Dicarinella primitiva to the first occurrence of Dicarinella concavata. The majority of planktic foraminifera researchers have believed that Turonian-Coniacian boundary cannot be determined based on planktic foraminifera, but some others believed that the first occurrence of Marginotruncana sinuosa has been shown in Turonian-Coniacian boundary [26][27][28]. Robaszynski F. and Caron M. [17] recorded the first occurrence of both Dicarinella primitiva and Dicarinella concavata in the late Turonian after correlation with ammonite's species Subprionocyclus neptuni.…”
Section: First Marker: Dicarinella Primitivamentioning
confidence: 99%
“…Caron M. [16] established this zone to represent the early Coniacian and occupy the interval from the first occurrence of Dicarinella primitiva to the first occurrence of Dicarinella concavata. The majority of planktic foraminifera researchers have believed that Turonian-Coniacian boundary cannot be determined based on planktic foraminifera, but some others believed that the first occurrence of Marginotruncana sinuosa has been shown in Turonian-Coniacian boundary [26][27][28]. Robaszynski F. and Caron M. [17] recorded the first occurrence of both Dicarinella primitiva and Dicarinella concavata in the late Turonian after correlation with ammonite's species Subprionocyclus neptuni.…”
Section: First Marker: Dicarinella Primitivamentioning
confidence: 99%
“…Although M. testudinarius has a global distribution, it is virtually restricted to relatively shallow water chalks and is absent in deeper water and most clastic facies (Gale et al, 2008). Marks (1984) noted that stratigraphically diagnostic planktonic foraminifera of the Dicarinella lineage are absent from the Aquitaine sections but suggested that the extinction of Dicarinella asymetrica provided a widely identifiable marker for the top of the Santonian in deeper water Tethyan successions. Following the work of Premoli and Premoli Silva and Sliter (1995), it has been demonstrated that the base of magnetochron C33r is approximately coincident with the highest occurrence of D. asymetrica in the Scaglia Rossa at Gubbio, Italy.…”
Section: Historical Backgroundmentioning
confidence: 99%